1985
DOI: 10.1128/jb.161.3.1002-1009.1985
|View full text |Cite
|
Sign up to set email alerts
|

Cell-bound and secreted proteases of Serratia marcescens

Abstract: Exoprotease of Serratia marcescens ATCC 25419 is exceptional among members of the family Enterobacteriaceae in that it is secreted in large amounts by viable cells into the culture medium. Labeling of cells with radioactive amino acids revealed no intracellular protein that could be precipitated with antibodies raised against purified exoproteases. With substances known to interfere with the excretion of some proteinstosyl-L-lysine chloromethyl ketone, phenethyl alcohol, procaine, and sodium azide-and with rif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…They may arise from separate genes, by post-translational modification or, as seems likely for some bands, by partial proteolysis. A similar problem exists in Serratia marcescens, where the 3 extracellular proteases have been shown to be closely related by sequence and serological studies [10].…”
Section: Discussionmentioning
confidence: 89%
“…They may arise from separate genes, by post-translational modification or, as seems likely for some bands, by partial proteolysis. A similar problem exists in Serratia marcescens, where the 3 extracellular proteases have been shown to be closely related by sequence and serological studies [10].…”
Section: Discussionmentioning
confidence: 89%
“…It was reported that a clinical isolate, kums 3958 strain, produced four types of protease (11) and two types of nuclease (15). Another reported that there were two forms of protease, i.e., intracellular form and exoform (14), though the types of the protease and the nuclease in the forms of the vesicles were not investigated. The extent of the participation of the vesicles in the secretion of the two enzymes seemed to be different from each other, because the highest activity of the protease was found in the supernatant fraction whereas that of the nuclease was found in the vesicle fraction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of proteins to the external medium is an unusual process in E. coll. The a-haemolysin produced by some strains seems to be one of the few exceptions [1]. When heterospecific secretable proteins are cloned in E. coli, they are mostly not secreted, and remain in the periplasmic space [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The a-haemolysin produced by some strains seems to be one of the few exceptions [1]. When heterospecific secretable proteins are cloned in E. coli, they are mostly not secreted, and remain in the periplasmic space [1][2][3][4][5][6]. A few cases have recently been reported in which foreign proteins appear to be secreted by E. coli [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%